Association of Sociodemographic Characteristics with the Time Spent in Occupational Activities of Older Persons in Malaysia - Ker, Ke Jun; Harun, Dzalani; Ismail, Siti Fairuz; Abdul Rahim, Nor Diana; Mohd Rasdi, Hanif Farhan; Ishak, Ismarulyusda (Malaysian Journal of Medical Sciences, 2025)
Background: The rate of population ageing is increasing far more quickly than in the past, making active ageing a critical focus. Occupational activities are the daily tasks performed by individuals and are closely related to well-being. Research on sociodemographic factors associated with the time spent in occupational activities by older persons in Malaysia is limited. Understanding these patterns can help policymakers and healthcare providers tailor interventions to support different demographic groups among older persons. The occupational activities examined in this study were personal care, employment-related, education, domestic, childcare, purchasing, voluntary, social, and leisure activities. The objective of this study was to identify the differences in the time spent by older persons in occupational activities based on sociodemographic factors.Methods: A cross-sectional study involving 270 older persons from activity centres for older persons in Klang Valley was conducted using the Modified Occupational Questionnaire-Malay version and analysed using Mann-Whitney U test and Kruskal–Wallis test.Results: Findings show significant differences in time spent on domestic activities based on employment status (P = 0.046), employment-related activities based on type of housing and household size (P = 0.034; P = 0.047), and leisure activities based on household size (P = 0.006), while social activities differed based on gender (P = 0.038) were observed. Working older persons engaged more in domestic activities than non-working older persons; women engaged more frequently in social activities than men. A significant difference was also found in the time spent on employment-related activities between living in high-end and affordable housing.Conclusion: Tailoring interventions based on these factors is crucial for promoting active ageing and enhancing the well-being of older persons.